Cops and Robbers on Graphs Based on Designs - Bonato, Anthony; Burgess, Andrea (Journal of combinatorial designs, 2013)
We investigate the cop number of graphs based on combinatorial designs. Incidence graphs, point graphs, and block intersection graphs are studied, with an emphasis on finding families of graphs with large cop number. We generalize known results on Meyniel extremal families by supplying bounds on the incidence graphs of transversal designs, certain G‐designs, and BIBDs with λ≥1. Families of graphs with diameter 2, C4‐free, and with unbounded chromatic number are described with the conjectured asymptotically maximum cop number.